Implementasi Asas Pelayanan Publik di Biro Hukum Sekertariat Provinsi Kalimantan Tengah - Syahrul Ikhsan; Kamal Hasuna; M. Khairul Amin; Wahdini Wahdini; Muskhan Adnan; Dea Helmia Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to explore and analyze the implementation of public service principles in the Legal Bureau of the Central Kalimantan Provincial Secretariat. The method used is qualitative research with a descriptive approach, which aims to provide an in-depth understanding of public service practices applied in the agency. Data were obtained through in-depth interviews with related parties, direct observation, and documentation studies. The results of the study indicate that the implementation of public service principles such as transparency, accountability, responsiveness, and participation in the Legal Bureau of the Central Kalimantan Provincial Secretariat has been carried out well, although there are several challenges faced, such as limited human resources and adequate infrastructure. The improvement efforts made include increasing employee capacity and utilizing information technology to accelerate the service process. This study provides an important contribution in understanding the dynamics of public services in the legal sector and becomes a consideration for the improvement and development of the service system at the provincial government level. It is hoped that this study can be a reference for further research and to improve the quality of public services in Central Kalimantan.